Development of a Predictive Modeling for Performance Evaluation of Disc and Hoe Tine Furrow Openers Under Semi-Arid No-Tillage Conditions - Al-Totonjy, Mahmood Shaker (American Journal of Botany and Bioengineering, 2026)
No-till farming is a conservation agriculture strategy aimed at protecting natural resources in semi-arid environments. This study focuses on analyzing the performance of the two main groove opening systems: disc and knife, and developing predictive models for their performance. Field experiments were conducted in a randomized complete block design (RCBD) to evaluate the effect of hatch type, operational speed (4-8 km/h), and soil moisture (12-18%) on key performance indicators. The results revealed the superiority of Al-Fateh Al-Sakini in achieving a higher uniformity of seed depth (with a lower standard deviation of 22%), especially in dry cohesive soil. In contrast, the disc opener demonstrated superior crop residue cutting efficiency (>95%) and reduced soil disturbance, with up to 28% lower pulling force requirements. High-resolution regression models (R² > 0.85) were built to predict performance. The research concludes that choosing the ideal conqueror depends on administrative priorities. The disc type is the most efficient and reliable option in semi-arid conditions with high residues, while the knife-threader provides better seeding depth performance in cohesive soils at the expense of higher energy consumption.